2018
DOI: 10.5586/aa.1742
|View full text |Cite
|
Sign up to set email alerts
|

Modeling hay fever risk factors caused by pollen from Ambrosia spp. using pollen load mapping in Ukraine

Abstract: The paper provides a simulation of the occurrence of <em>Ambrosia</em> pollen in Ukraine both in terms of a determination of the regions with high pollen concentrations and the time when the high pollen load occurs. Simulation was performed using the SILAM system and the following pollen mapping using the Grid Analysis and Display System. Simulation results were compared with the aerobiological data available from six monitoring stations in Ukraine. A decrease in the concentrations of <em>Amb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Recently Florincescu et al [12] published the first data regarding sensitization to ragweed in patients with allergic rhinitis from Southern part of Romania, reporting a higher percentage of sensitization (48.8%) compared to our study. The highest levels of airborne ragweed pollen in Europe are known to have been recorded in Hungary and Ukraine [6,15], which may explain the higher rate of sensitization from the NW region compared to the Central region. High levels of ragweed pollen have also been recorded in the Black Sea region of Turkey [15,16], which may explain a higher rate of sensitization to ragweed in the Southern region of Romania reported by Florincescu et al [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently Florincescu et al [12] published the first data regarding sensitization to ragweed in patients with allergic rhinitis from Southern part of Romania, reporting a higher percentage of sensitization (48.8%) compared to our study. The highest levels of airborne ragweed pollen in Europe are known to have been recorded in Hungary and Ukraine [6,15], which may explain the higher rate of sensitization from the NW region compared to the Central region. High levels of ragweed pollen have also been recorded in the Black Sea region of Turkey [15,16], which may explain a higher rate of sensitization to ragweed in the Southern region of Romania reported by Florincescu et al [12].…”
Section: Discussionmentioning
confidence: 99%
“…The highest levels of airborne ragweed pollen in Europe are known to have been recorded in Hungary and Ukraine [6,15], which may explain the higher rate of sensitization from the NW region compared to the Central region. High levels of ragweed pollen have also been recorded in the Black Sea region of Turkey [15,16], which may explain a higher rate of sensitization to ragweed in the Southern region of Romania reported by Florincescu et al [12]. Looking to all this available data regarding sensitization to ragweed in Romania, we may assume that allergic rhinitis to ragweed could be more frequently observed in Western and Southern parts of the country.…”
Section: Discussionmentioning
confidence: 99%
“…S6; Supplementary materials). Nevertheless, ragweed and mugwort pollen may be airborne at the same time, what is also true for the area between the Pannonian Plain (Timisoara) and Vinnytsia (Ukraine) (Stępalska et al, 2017), where sensitization to pollen of both taxa has been confirmed (Ianovici and Sirbu, 2007;Afonin et al, 2018;Rodinkova et al, 2018). In many European regions, the problem of co-sensitization or cross-sensitization to mugwort and ragweed pollen exists, making the diagnostics of the primary sensitizing allergen a quite difficult task and consequently the implementation of the proper immunotherapy (Asero et al, 2014).…”
Section: Aprilmentioning
confidence: 88%
“…The species became naturalized in Europe, and currently, it is widespread as an invasive species (Stevens 2001 ). The sensitization rate against ragweed pollen is high among humans and is compared to that of grass pollen and is expected to increase due to plant migration across Europe (Rodinkova et al 2018 ; Buters et al 2015 ). The major allergen of ragweed is Amb a 1, a member of the pectatelyases that catalyzes the breakdown of pectin (the major plant cellular wall component).…”
Section: Methodsmentioning
confidence: 99%